Vis Creativa: a singularidade da vivência criadora no pensamento nietzschiano - Adami, Jackson Daniel (2016)
Much is said about how the Nietzschean philosophy is related to the theme of art. This research will try to further explore this relation. We will take the theme of art in Nietzsche's philosophy, in a broad sense, as a guide and launch the challenges of getting lost in the multiplicity of his topics when the relevance of art seems to capsize in his writings. Thus, the central point involved in this research is the investigation of the art status, in your broad sense, in Nietzschean thought on his works The Birth of Tragedy (1872), Human, All Too Human (1878) and The Gay Science (1882). For this purpose, first we will carefully analyze the influence of art in the thought of the young Nietzsche. Thus, we will treat the Apollonian-Dionysian union, the experience of the tragic propitiated by such a union and how it is interfered on metaphysical conceptions. Later, we will treat metaphysics depuration undertaken by Nietzsche on his work Human, All Too Human, in which the thinker seeks the anti-dogmatism and the rigor of the scientific stance as the antidotes to the romanticism and idealism that his philosophy was subjected in his inaugural stage. At this stage of the research we will see how the philosopher attenuated the importance of art in his writings. In an effort to keep the connecting thread of the art as a guide, we will explore the conceptions of art present, often covertly, on the work The Gay Science. Therein the art seems to return with new vigor, and even remote from the metaphysical conceptions, which guaranteed him support, art resurfaces with more depth than the thought of the young Nietzsche. On this resurgence we can associate the knowledge with the living (Erlebnis) and the self creation. About living (Erlebnis) we will explore the singularity inherent in it due to the several and peculiar power arrangements of existence. Finally, we will approach the topic of vis creativa (creative power), a term coined by Nietzsche and little explored that seems to lose its most own brilliance at the strength of will to power conceptions. The themes of Nietzsche's illness and loss of self (Selbstlostsigkeit) are also treated.